2021
DOI: 10.1101/2021.09.27.21264151
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Understanding the evidence for climate concerns, negative emotions and climate-related mental ill-health in young people: a scoping review

Abstract: Background: Human-induced climate change represents a serious threat to human health, including mental health, due to both the traumatising effects of extreme climate events and the psychological effect of worry about climate change. The present scoping review aims to systematically search and synthesise original research related to mental health and climate-related concerns, negative emotions and mental ill-health in young people. Findings will help to understand the current landscape, gaps in the literature,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…However, emotions related to climate change are nuanced and complex. Ramadan et al (2021), identified ten different conceptualizations of the negative emotional response to climate change, including climate anxiety, climate change worry, eco-anxiety, and ecoparalysis. Stanley et al (2021) further explored the differing implications and impacts of eco-depression, eco-anger, and eco-anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…However, emotions related to climate change are nuanced and complex. Ramadan et al (2021), identified ten different conceptualizations of the negative emotional response to climate change, including climate anxiety, climate change worry, eco-anxiety, and ecoparalysis. Stanley et al (2021) further explored the differing implications and impacts of eco-depression, eco-anger, and eco-anxiety.…”
Section: Introductionmentioning
confidence: 99%